Exploring Direct and Indirect Influences of Physical Work Environment on Job Satisfaction for Early-Career Registered Nurses Employed in Hospitals - Djukic, M.; Kovner, C.; Brewer, C.; Fatehi, F.; Greene, William (2014)
We explored direct and indirect influences of physical work environment on job satisfaction in a nationally representative sample of 1,141 early-career registered nurses. In the fully specified model, physical work environment had a non-significant direct effect on job satisfaction. The path analysis used to test multiple indirect effects showed that physical work environment had a positive indirect effect (p<.05) on job satisfaction through ten variables: negative affectivity, variety, workgroup cohesion, nurse-physician relations, quantitative workload, organizational constraints, distributive justice, promotional opportunity, local and non-local job opportunities. The findings make important contributions to the understanding of the relationship between physical work environment and job satisfaction. The results can inform health care leaders' insight about how physical work environment influences nurses' job satisfaction. © 2014 Wiley Periodicals, Inc.